1999
DOI: 10.1128/jcm.37.4.1045-1048.1999
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori Can Be Induced To Assume the Morphology of Helicobacter heilmannii

Abstract: Cultures of Helicobacter pylori obtained from the American Type Culture Collection (strain 43504) were grown as isolated colonies or lawns on blood agar plates and in broth culture with constant shaking. Examination of bacterial growth with Gram-stained fixed preparation and differential interference contrast microscopy on wet preparations revealed that bacteria grown on blood agar plates had a morphology consistent with that normally reported for H. pylori whereas bacteria from broth cultures had the morpholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 11 publications
(11 reference statements)
3
13
0
Order By: Relevance
“…In all three media with serum, as the culture aged, the spiral bacteria were replaced by U forms, coccoid bacteria and, predominantly, by very long bacteria, with a filamentous morphology; all these bacteria with different shapes presented a concomitant loss of viability, throughout time. The long spiral morphology was already reported by Fawcett et al (25), who referred that growth in liquid media with shaking can induce H. pylori to assume a long spiral morphology resembling that described for H. heilmanni. Therefore, culture conditions can be responsible for the change in morphology.…”
Section: Discussionsupporting
confidence: 68%
“…In all three media with serum, as the culture aged, the spiral bacteria were replaced by U forms, coccoid bacteria and, predominantly, by very long bacteria, with a filamentous morphology; all these bacteria with different shapes presented a concomitant loss of viability, throughout time. The long spiral morphology was already reported by Fawcett et al (25), who referred that growth in liquid media with shaking can induce H. pylori to assume a long spiral morphology resembling that described for H. heilmanni. Therefore, culture conditions can be responsible for the change in morphology.…”
Section: Discussionsupporting
confidence: 68%
“…Further, H. pylori from broth cultures have been reported to show the morphological appearance of H. heilmannii. 8 In the present study, the localization of H. heilmannii was shown by toluidine blue staining and electron microscopy of Epon embedded-specimens, and crossreactivity with the monoclonal antibody against H. pylori. Development of more specific methods is therefore needed to clarify the actual significance of H. heilmannii in the gastric pathophysiology.…”
Section: Discussionmentioning
confidence: 52%
“…In these latter cases, it is unclear if the bacteria with HHLO morphology represented H. pylori rather than other Helicobacter species. It has been demonstrated that H. pylori can be induced to assume a "H. heilmannii"-like morphology [38]. Also, other yet unknown Helicobacter species could be involved in HHLO-induced disease and as such could have not been detected in this study.…”
Section: Discussionmentioning
confidence: 69%